2017
DOI: 10.1007/s00709-017-1120-1
|View full text |Cite
|
Sign up to set email alerts
|

Integument cell gelatinisation—the fate of the integumentary cells in Hieracium and Pilosella (Asteraceae)

Abstract: Members of the genera Hieracium and Pilosella are model plants that are used to study the mechanisms of apomixis. In order to have a proper understanding of apomixis, knowledge about the relationship between the maternal tissue and the gametophyte is needed. In the genus Pilosella, previous authors have described the specific process of the “liquefaction” of the integument cells that surround the embryo sac. However, these observations were based on data only at the light microscopy level. The main aim of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…This results in the separation of the protoplast from the cell wall, and excessive accumulation of mucilage in periplasmic space induces the shrinkage of the protoplast. Eventually, the mucilage fills in the space between the cell wall and shrinking and degenerating protoplast, and integumental cells are replaced with mucilage, which contributes to the unobstructed growth of the embryo [13,[15][16][17][18]. On the contrary, our study showed that in tomato, the mucilage zone was localized distantly from the dying integumental cells, and was formed by the endothelium and the endosperm.…”
Section: Pcd Of the Integument Of Tomato Ovulesmentioning
confidence: 62%
See 2 more Smart Citations
“…This results in the separation of the protoplast from the cell wall, and excessive accumulation of mucilage in periplasmic space induces the shrinkage of the protoplast. Eventually, the mucilage fills in the space between the cell wall and shrinking and degenerating protoplast, and integumental cells are replaced with mucilage, which contributes to the unobstructed growth of the embryo [13,[15][16][17][18]. On the contrary, our study showed that in tomato, the mucilage zone was localized distantly from the dying integumental cells, and was formed by the endothelium and the endosperm.…”
Section: Pcd Of the Integument Of Tomato Ovulesmentioning
confidence: 62%
“…The plasma membranes at the inner cell walls of both tissues bordering each other had a sinuate contour, most evident in the endosperm cells. According to many authors, such ultrastructural composition is common for cells producing polysaccharide mucilage [13][14][15][16][17][18].…”
Section: Normal Tomato Phase Of Early Multicellular Embryomentioning
confidence: 99%
See 1 more Smart Citation
“…The acidic polysaccharides composing the mucilage of M. pubescens are compartmentalized in vacuoles formed by the fusion of dictyosome vesicles. Dictyosomes, associated with the synthesis of strongly hydrophilic acidic polysaccharides having a fibrillar appearance (when viewed with transmission electron microscopy) are well documented in seeds (McFarlane et al., ; Young et al., ; Haughn and Western, ; Voiniciuc, ; Płachno et al., ; Phan and Burton, ) and other mucilage‐secreting structures (Mercadante‐Simões and Paiva, ; Ballego‐Campos and Paiva, ; Gonçalves et al., ; Rodrigues et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Seed development and the chemical constituents of the mucilaginous layer in M. pubescens have been previously studied (Oliveira et al., , ), but neither the mucilaginous secretions nor their ecological roles have yet been investigated. Considering the economic potential of seed mucilages (Plachno et al., ; Phan and Burton, ) and the structural peculiarities of secretory cells (Haughn and Western, ; Kreitschitz and Gorb, ), numerous lines of investigation still need to be pursued. The present work was designed to study the development and function of the mucilage of M. pubescens seeds to (1) relate structural and ultrastructural aspects of the mucilage to secretion and hydration mechanisms and (2) to evaluate the role of the mucilage capsule in seed germination.…”
mentioning
confidence: 99%